2008
DOI: 10.1080/15572536.2008.11832494
|View full text |Cite
|
Sign up to set email alerts
|

The effects of arbuscular mycorrhizal fungal inoculation at a roadside prairie restoration site

Abstract: Arbuscular mycorrhizal fungi (AMF) may play an important role in ecological succession, but few studies have documented the effectiveness of mycorrhizal inoculation at restoration/reclamation sites. At a roadside prairie restoration in Shakopee, Minnesota, we compared AMF root colonization and resulting vegetative cover among four inoculation treatments. After 15 mo of growth, we found that AMF colonization was high in all treatments but was significantly higher in treatments that received AMF inoculum propaga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
30
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…However, there was no effect of age on the colonization rate or growth in a later successional species, little bluestem (schizachyrium scoparium). Our results may be due to the fact that while phosphate levels on our restoration sites were higher than those on remnants, they were still much lower than those found by others where mycorrhizae are either inhibited or fail to have an effect on plant performance (White et al 2008). Our data agree with other findings that show the rate of mycorrhizal colonization is not necessarily a good predictor of plant growth (Smith et al 1998, Smith et al 2004, Busby et al 2011.…”
Section: Discussionsupporting
confidence: 85%
“…However, there was no effect of age on the colonization rate or growth in a later successional species, little bluestem (schizachyrium scoparium). Our results may be due to the fact that while phosphate levels on our restoration sites were higher than those on remnants, they were still much lower than those found by others where mycorrhizae are either inhibited or fail to have an effect on plant performance (White et al 2008). Our data agree with other findings that show the rate of mycorrhizal colonization is not necessarily a good predictor of plant growth (Smith et al 1998, Smith et al 2004, Busby et al 2011.…”
Section: Discussionsupporting
confidence: 85%
“…White et al (2008) reported that AMF inoculation at their Minnesota (USA) grassland restoration did not increase biomass production, and they attributed the lack of effect to adequate initial propagule densities at their latesuccession stage restoration. However, landscapes available for restorations are frequently highly disturbed and may have reduced propagule numbers and AMF infectivity (Smith et al 1998).…”
Section: Discussionmentioning
confidence: 96%
“…In a comparison of post-agricultural fields and adjacent unplowed prairie, Bever et al (2003) reported a shift in AM fungal species composition that favored weedy fungal species in the post-agricultural sites and hypothesized that this shift in fungal species may impede restoration and establishment of native grasses of the postagricultural lands. The applications of native prairie soil have been shown to increase the establishment success of native plant species, at least in part, due to restoration of the native AM fungal communities (Smith et al 1998;White et al 2008;Bever et al 2009). If Bothriochloa alters the AM fungal communities, providing a competitive advantage and inhibiting the obligate symbiosis of the native grasses, restoring AM fungal communities through additions of native prairie inoculum that promote the success of native species may be an important management consideration in areas where Bothriochloa is eradicated and the restoration of native species is in progress.…”
Section: Discussionmentioning
confidence: 98%